Pendampingan dan Strategi Guru dalam Menumbuhkan Semangat Belajar Anak Sekolah Minggu Melalui Metode Bermain dan Bernyanyi di Pulau Teluk Nipah - Selvyen Sophia; Rini Sumanti Sapalakkai; Dewi Lidya S; Irfan Feriando Simanjuntak; Septerianus Waruwu (Sekolah Tinggi Teologi Real Batam, 2022)
The Sunday school teacher is God's partner in educating Sunday school children, regarding Christian Religious Education for which he has a responsibility, to seek the salvation of the souls of every student in his class. For this reason, Sunday school teachers need to foster children's enthusiasm in learning God's Word, so that the children's spiritual growth process is well accommodated. But often what happens is the lack of attention from the children so that it becomes an obstacle in conveying God's Word. So Sunday school teachers need to do a strategy for this. One of the Sunday school teacher strategies to foster children's enthusiasm in learning God's Word used in this article, is by playing and singing methods. The purpose of this service is to foster children's enthusiasm for learning by bringing children to know Jesus as Savior, and making children able to have noble character according to the teachings of Christ. By teaching songs, making games, and giving gift packages to children, it is hoped that children can participate in these learning activities and can absorb every story of God's Word that is preached by the Sunday school teacher.Keywords: learning; played; sing; Sunday school teacher; strategy; Nipah Bay Island AbstrakGuru sekolah minggu merupakan mitra Allah dalam mendidik anak sekolah minggu, mengenai Pendidikan Agama Kristen yang mana ia memiliki tanggungjawab, untuk mengusahakan keselamatan jiwa setiap murid yang ada di dalam kelasnya. Untuk itulah, guru sekolah minggu perlu menumbuhkan semangat anak dalam belajar Firman Tuhan, dengan begitu proses pertumbuhan rohani anak-anak terakomodasi dengan baik. Namun seringkali yang terjadi adalah kurangnya perhatian dari anak-anak sehingga menjadi penghambat dalam menyampaikan Firman Tuhan. Maka guru sekolah minggu perlu melakukan strategi akan hal tersebut. Salah satu strategi guru sekolah minggu untuk menumbuhkan semangat anak dalam belajar Firman Tuhan yang dipakai dalam artikel ini, yaitu dengan metode bermain dan bernyanyi. Tujuan dari pengabdian ini adalah menumbuhkan semangat anak belajar dengan membawa anak-anak mengenal Yesus sebagai Juruselamat, serta menjadikan anak-anak dapat berakhlak mulia sesuai dengan ajaran Kristus. Dengan mengajarkan lagu, membuat games, dan pemberian paket hadiah kepada anak, diharapkan anak dapat berpartisipasi dalam kegiatan belajar tersebut serta dapat menyerap setiap cerita Firman Tuhan yang diberitakan oleh guru sekolah minggu.Kata kunci: belajar; bermain; bernyanyi; guru sekolah minggu; strategi; pulau Teluk Nipah